(d): \(y=\left(m^2+3\right)x+4\)
=>\(\left(m^2+3\right)x-y+4=0\)
Khoảng cách từ O(0;0) đến (d) là:
\(d\left(O;\left(d\right)\right)=\dfrac{\left|0\cdot\left(m^2+3\right)+0\cdot\left(-1\right)+4\right|}{\sqrt{\left(m^2+3\right)^2+\left(-1\right)^2}}\)
\(=\dfrac{4}{\sqrt{\left(m^2+3\right)^2+1}}\)
\(m^2+3>=3\forall m\)
=>\(\left(m^2+3\right)^2>=9\forall m\)
=>\(\left(m^2+3\right)^2+1>=10\forall m\)
=>\(\sqrt{\left(m^2+3\right)^2+1}>=\sqrt{10}\forall m\)
=>\(\dfrac{4}{\sqrt{\left(m^2+3\right)^2+1}}< =\dfrac{4}{\sqrt{10}}\forall m\)
=>\(d\left(O;\left(d\right)\right)< =\dfrac{4}{\sqrt{10}}\forall m\)
Vậy: Khoảng cách từ O(0;0) đến (d) lớn nhất bằng \(\dfrac{4}{\sqrt{10}}=\dfrac{4\sqrt{10}}{10}=\dfrac{2\sqrt{10}}{5}\) khi m=0